Wideband symmetric near-field radiation pattern of sleeve dipole antenna by connecting additional ferrite-loaded wire - Cho, Jae-Hyoung; Kim, Se-Yun (INST ENGINEERING TECHNOLOGY-IET, 2015)
A scaled-down laboratory experiment has been performed in a well-controlled situation to find an enhanced rule for detecting a man-made underground tunnel by employing a cross-borehole frequency-swept radar system. A sleeve dipole antenna, fed by a coaxial cable passing inside its upper arm, is employed to easily put and pull it along an air-filled thin and long glass tube in scaled-down experiments. The tube-guided wave along the coaxial cable can be suppressed by ferrite-loading along the coaxial cable. However, the dipole antenna fed by the ferrite-loaded coaxial cable provides an asymmetrical radiation pattern in the near-field region. To improve the symmetry of its near-field radiation pattern, an additional ferrite-loaded wire is connected to the lower arm of the sleeve dipole antenna. According to the scattering measurement by an air-filled circular cylinder, the additional ferrite-loaded wire improves the symmetry of the electric field by more 30 dB in the frequency range of 1.5-3 GHz.
Keywords: RADAR